2023
DOI: 10.3389/fpsyg.2022.1026821
|View full text |Cite
|
Sign up to set email alerts
|

Documenting the mental health climate in correctional work and the realities of suicide

Abstract: Public safety personnel are at an elevated risk for suicidal thoughts and behaviors relative to the general public. Correctional workers in particular report some of the highest prevalence of suicidal thoughts and behaviors. To better understand this phenomenon, the current study draws on qualitative, open-ended survey response data (n = 94) that explores three distinct themes (occupational environment, lack of support, social silence) and how entrenched notions of mental health stigma and occupational culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Respondents described how correctional work wears on them, including psychological, physical, and emotional effects as well as the various ways these effects spill over into their personal and family lives. As other research on correctional services has demonstrated ( Johnston et al, 2021 , 2022b ; Johnston and Ricciardelli, 2023 ); participants shared how mental health and attending to mental health is still stigmatized within the profession and the need to overcome this stigma to adequately address the mental health concerns that arise from operational and organizational stressors. Here, breaking down barriers to mental health treatment seeking is essential to encourage employees to come forward and seek intervention without fear of occupational or personal repercussions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Respondents described how correctional work wears on them, including psychological, physical, and emotional effects as well as the various ways these effects spill over into their personal and family lives. As other research on correctional services has demonstrated ( Johnston et al, 2021 , 2022b ; Johnston and Ricciardelli, 2023 ); participants shared how mental health and attending to mental health is still stigmatized within the profession and the need to overcome this stigma to adequately address the mental health concerns that arise from operational and organizational stressors. Here, breaking down barriers to mental health treatment seeking is essential to encourage employees to come forward and seek intervention without fear of occupational or personal repercussions.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the prevalence of mental health concerns among correctional workers that can be explained, to varying degrees, by operational and organizational factors within correctional services, mental health is still stigmatized in the profession, despite on-going suggestions for improvement and increased recognition of the mental health plights of correctional workers, in Canada especially (see Johnston et al, 2022b ; Johnston and Ricciardelli, 2023 ). Johnston et al (2021) have illustrated how stigma materializes within correctional services when mental health becomes framed as a personal problem to be resolved by the individual, rather than through a mutual partnership between the worker and organization.…”
Section: Introductionmentioning
confidence: 99%